PENGARUH PENETAPAN HARGA, EFEKTIFITAS IKLAN DAN STRATEGI KEMASAN TERHADAP BRAND LOYALTY PRODUK DANONE AQUA - Pramelani, - (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2015)
ABSTRACTWith increasingly fierce competition in the industry bottled mineral water, every brand perform a variety of ways to win. Products Danone Aqua has become a generic brand, but will need to create a strong brand loyalty because many bottled water brands that offer low prices or attractive packaging. Thus, the purpose of this study was to analyze the effect of pricing, advertising effectiveness and strategy of packaging on brand loyalty product Danone Aqua partially or simultaneously and analyze the most dominant factor in influencing brand loyalty. The sample was 130 people and carried out questionnaires to the Student of Academy Communication Bina Sarana Informatika with convenience sampling method. Data analysis technique used is multiple linear regression with the results obtained indicate pricing significant and positive impact on brand loyalty, advertising effectiveness significant and positive impact on brand loyalty, and packaging strategies significant and positive impact on brand loyalty. Effectiveness of advertising is the most dominant as the most effective in increasing brand loyalty. While simultaneously pricing, advertising effectiveness and packaging strategies significant and positive impact on brand loyalty. Analysis of the coefficient determination on adjusted R Square of 0.497 which means donations pricing, advertising effectiveness, and packaging strategy is 49.7%, while the remaining 50.3% is influenced by other factors not examined. Keywords: Pricing, Advertising Effectiveness, Packaging Strategies and Brand Loyalty